2002
DOI: 10.1046/j.1467-2494.2002.00153.x
|View full text |Cite
|
Sign up to set email alerts
|

A synthetic hexapeptide (Argireline) with antiwrinkle activity

Abstract: Botulinum neurotoxins (BoNTs) represent a revolution in cosmetic science because of their remarkable and long-lasting antiwrinkle activity. However, their high neurotoxicity seriously limits their use. Thus, there is a need to design and validate non-toxic molecules that mimic the action of BoNTs. The hexapeptide Ac-EEMQRR-NH(2) (coined Argireline) was identified as a result of a rational design programme. Noteworthy, skin topography analysis of an oil/water (O/W) emulsion containing 10% of the hexapeptide on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
118
0
12

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(130 citation statements)
references
References 14 publications
(36 reference statements)
0
118
0
12
Order By: Relevance
“…It is concluded that acetyl hexapeptide-3 is an effective anti-aging compound as already mentioned by Blanes-Mira et al (2002). The author, using silicone replicas, observed that topical application of an emulsion containing the peptide attenuated the depth of wrinkles in the periocular region after 30 days of treatment, when compared with the vehicle.…”
Section: Corneometermentioning
confidence: 70%
See 2 more Smart Citations
“…It is concluded that acetyl hexapeptide-3 is an effective anti-aging compound as already mentioned by Blanes-Mira et al (2002). The author, using silicone replicas, observed that topical application of an emulsion containing the peptide attenuated the depth of wrinkles in the periocular region after 30 days of treatment, when compared with the vehicle.…”
Section: Corneometermentioning
confidence: 70%
“…An in vitro study demonstrated that acetyl hexapeptide-3 inhibits neurotransmitter release with a potency similar to that of botulinum neurotoxin, although as expected, it displayed much lower efficacy than the neurotoxin (Sivilia et al, 2008;Blanes-Mira et al, 2002).…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…Etki mekanizması üzerinde yapılan çalışmalar heksapeptitlerinBotulinum nörotoksinlerine (BoNT) benzer şekilde nörotransmitter salımını inhibe ettiklerini ancak etkisinin çok daha düşük olduğunu göstermiştir. Sonuç olarak, elde edilen bulgular hekzapeptitlerin toksik olmadığı ve kırışıklık önleyici moleküller olduğunu kanıtlamıştır 57 . Matrikin kompleksi (Matrixyl ™ 3000); palmitoil oligopeptit ve palmitoiltetrapeptit-7 adlı iki matrikinin bileşiminden oluşmaktadır.…”
Section: Doğal Veya Sentetik Kökenli Peptitler Ve Türevleriunclassified
“…Several peptide inhibitors have been developed for this purpose (Gutierrez et al, 1995(Gutierrez et al, , 1997Ferrer-Montiel et al, 1998;Cornille et al, 1995;Blanes-Mira et al, 2003Apland et al, 2003;Blanes-Mira et al, 2002;Jung et al, 2008). Most peptide inhibitors were screened from SNARE-patterned sequences.…”
Section: Introductionmentioning
confidence: 99%